Pengaruh Kompetensi Pedagogik dan Motivasi Kerja Guru terhadap Prestasi Belajar Siswa Kelas V SD di Kecamatan Langowan Timur - Tunas, Koni Olive; Lumapow, Harol Reflie; Mongdong, Romi Junior (Jurnal Simki Pedagogia, 2025)
This study aims to analyze the influence of Pedagogical Competence and Teacher Work Motivation on the Learning Achievement of Grade V Elementary School Students in Langowan Timur District. This study used non-probability sampling with saturated sampling techniques, involving 75 students as samples. Data were analyzed using descriptive statistics, correlation, reliability, normality, linearity, simple regression, and multiple regression with the help of SPSS 25. The results showed that there was a significant direct influence of pedagogical competence on the learning achievement of grade V students p = 0.000 <0.05 and the Determinant Coefficient (R2) of 0.70% which means that pedagogical competence explains 0.70% of the variation in student learning achievement. Teacher Work Motivation has a significant effect on student learning outcomes with p = 0.000 <0.05 and R2 = 0.84% ​​indicating that motivation explains 0.84% ​​of the variation in student learning achievement. Simultaneously, the influence of pedagogical competence and teacher work motivation both have a significant effect on student learning achievement with p = 0.000 < 0.05 and R2 = 0.97% which means that both variables explain the variation in the learning achievement of fifth grade students. The conclusion is the influence of pedagogical competence and teacher work motivation significantly on the learning achievement of fifth grade students of elementary school in East Langowan District.